(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The air we breathe is extremely contaminated these days. The car we drive is the second important factor. "Electric Vehicle" is the solution to the issue. However, in "1881," automobiles were initially powered by electricity. On the other hand, internal combustion engines that run on gasoline and diesel were created later in "1887" in order to increase power and efficiency. However, their exhaust air currently contributes significantly to global carbon emissions. Electric vehicles are now the greatest choice.